Ethical Leadership Evaluations After Moral Transgression: Social Distance Makes the Difference - Tumasjan, Andranik; Strobel, Maria; Welpe, Isabell M. 1975- (2011)
In light of continuing corporate scandals, the study of ethical leadership remains an important area of research which helps to understand the antecedents and consequences of ethical behavior in organizations. The present study investigates how social distance influences ethical leadership evaluations, and how in turn ethical leadership evaluations affect leader–member exchange (LMX) after a leader’s moral transgression. Based on construal level theory, we propose that higher social distance will lead to more severe evaluations of immoral behavior and therefore entail lower ethical leadership ratings. More- over, we hypothesize that ethical leadership will positively affect LMX. Participants read a scenario describing a moral situation in which a leader, who was presented in either high or low social distance, behaves unethically toward an employee. We tested our predictions using a structural equation modeling approach. As expected, participants in the high social distance condition judged leaders more harshly (i.e., they gave lower ethical leadership ratings) than in the low social distance condition. Thus, social distance moderated the extent to which leaders are perceived as ethical leaders after moral transgression. Moreover, in accordance with our proposition, ethical leadership ratings had a positive influence on LMX.
Keywords: Leader–member exchange; Moral Reasoning; Social distance; Construal level theory; Ethical Leadership